NUANSA HEGEMONIS ASOSIATIF DALAM PENAMAAN KULINER MASYARAKAT URBAN SURABAYA - Dian Purnama Sari (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2021)
The purpose of this research is to describe the associative meaning that is formed from the culinary name in Surabaya and to describe the hegemonic nuances inherent in it. This type of research is descriptive qualitative, the data source is the Surabaya urban community and the data is in the form of culinary names that were created. Researchers use a data analyzing corpus. The naming of urban culinary is full of associative meanings that have different connotations from culinary names in the past, representing the psychic condition of the community because naming is a medium of language which is a reflection of the brain and soul of the wearer, the nuances of capital hegemony around class differences, exploitation and oppression. reflected in the names of foods consumed by the urban community in Surabaya in particular. A hegemonic society has not yet reached the point of becoming a survivor, still lamenting the fate and associative baper through the culinary names it created. Efforts to build the community's mentality so as not to continue to feel like a hegomonic victim can be started with the creation of optimistic culinary phrases or terms.